FUNCTIONAL-SEMANTIC SIMILARITIES AND DIFFERENCES OF INTERNATIONAL VOCABULARY IN ENGLISH AND UZBEK - Kholikova Dilnoza Musurmon qizi (International Journal of Literature and Language Studies, 2026)
This article presents a comparative analysis of the functional-semantic characteristics of international vocabulary in English and Uzbek languages. Drawing on corpus-based evidence and lexicographic data, the study examines how international terms are semantically adapted, functionally deployed, and stylistically marked within each linguistic system. The analysis reveals that while both languages demonstrate openness to international lexical elements, they exhibit divergent patterns of semantic integration: English tends toward controlled metaphorical specialization, whereas Uzbek demonstrates expansive semantic broadening and hybrid morphological constructions. A systematic comparative table synthesizes key functional-semantic parameters, offering a structured framework for understanding cross-linguistic lexical adaptation. The findings contribute to contact linguistics, comparative lexicology, and translation studies.